Profesionalisme Guru di Era Digital ; Upaya dalam Meningkatkan Mutu Lembaga Pendidikan - Mudarris, Badrul (ALSYS, 2022)
This paper describes the efforts of MTs Pandean in improving the quality of its institutions through teacher professionalism in the digital era. The quality of educational institutions is closely related to teachers as educators who will prepare students in the digitalization era. To obtain valid and accountable data, the researcher conducted interviews with several informants using purposive sampling technique, which consisted of five people, namely Qodiri, S. Pd as the head of the madrasa, Nurul Huda, S. Pd as the deputy head, Hasan Bashri, S. Pd. I as the deputy head of the curriculum, Noviwahyu Ningtiyas, S.E, S. Pd, one of the teachers at the madrasa. The forms of efforts made at MTs Pandean are training to build digital literacy awareness, teacher working groups (KKG) to build an entrepreneurial spirit, and supervision to build teacher leadership and emotional intelligence. With the fulfillment of the teacher indicators of teacher professionalism at MTs Pandean, it is hoped that then it will be able to improve the quality of these educational institutions.